2017
DOI: 10.1007/s00044-017-2121-5
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and cytotoxic activities of short carbon chain unsaturated sucrose esters

Abstract: A library of C3-C5 unsaturated 6-O-sucrose esters have been investigated for their antibacterial, antifungal, and cytotoxic activities. Most of the target compounds showed good inhibitory activity against a variety of clinically and food contaminant important microbial pathogens. In particular, 6-O-methacryloyl sucrose 2 and 1′,2,3,3′,4,4′,6′-hepta-O-acetyl-6-O-methacryloyl sucrose 9 were the most active bactericides against all the tested bacteria with minimal inhibitory concentrations (MICs) ranging between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…Morin et al [67] and Siena et al [68] reported that, a variety of modified FAs are promising molecules in the treatment of cancers. Also, there were several studies dealing with anticancer, antimicrobial and anti-inflammatory activities of SE derivatives [69, 70]. Our results correlated with those reported by An and Feng [71], whose evaluated the antitumor activity of series of glucosyl esters derivatives against three cancer cells, human breast adenocarcinoma (MCF-7), human colon carcinoma (K562) and human hepatoma (HepG2).…”
Section: Resultssupporting
confidence: 88%
“…Morin et al [67] and Siena et al [68] reported that, a variety of modified FAs are promising molecules in the treatment of cancers. Also, there were several studies dealing with anticancer, antimicrobial and anti-inflammatory activities of SE derivatives [69, 70]. Our results correlated with those reported by An and Feng [71], whose evaluated the antitumor activity of series of glucosyl esters derivatives against three cancer cells, human breast adenocarcinoma (MCF-7), human colon carcinoma (K562) and human hepatoma (HepG2).…”
Section: Resultssupporting
confidence: 88%
“…Sucrosomial® iron is made of a ferric pyrophosphate core surrounded by a phospholipid matrix coated with the sucrose ester of fatty acids, sucrester (Gomez-Ramirez et al 2018 ). Some sucrose esters have been shown to have antimicrobial properties (Petrova et al 2017 ), however, whether this applies to sucrester is unclear and further research is needed to explain the beneficial effects of Sucrosomial® iron on the intestinal microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…been done on their application features [33], many concerns about the nature of these molecules remain unanswered [34], leaving room for further scientific investigation and practical studies. In this respect, in vitro antimicrobial tests, ADMET, and molecular docking of the synthesized rhamnopyranoside esters were conducted and reported herein.…”
Section: Introductionmentioning
confidence: 99%